Long-Term intraocular pressure changes in patients with neovascular age-related macular degeneration treated with Ranibizumab - Menke, Marcel N.; Salam, Adzura; Framme, Carsten; Wolf, Sebastian (S. Karger AG, 2013)
Background/Aims: To investigate the long-term effects of multiple intravitreal injections (IVTs) of ranibizumab (Lucentis) on intraocular pressure (IOP) in patients with neovascular age-related macular degeneration. Methods: In 320 eyes, IOP measurements were performed at baseline prior to injection and compared with IOP measurements of the last visit. Correlations between mean IOP change and total number of IVTs, visual acuity or patient age were tested. Results: The mean IOP increase was 0.8 ± 3.1 mm Hg (p < 0.0001). Seven eyes showed final IOP values between 22 and 25 mm Hg. The mean follow-up was 22.7 ± 14.1 months. No further correlations between IOP change and number of IVTs, visual acuity or patient age have been found. Conclusions: This study demonstrated a statistically significant IOP increase in patients treated with repeated injections of ranibizumab. However, IOP increase required no glaucoma treatment during the study. Therefore, repeated injections with ranibizumab can be considered safe with regard to long-term IOP changes in patients without ocular hypertension or glaucoma. Copyright © 2013 S. Karger AG, Basel.